The Evaluation and Treatment of Delayed Ejaculation. Issue 3 (8th May 2014) - Shin, Daniel H.; Spitz, Aaron
Abstract Introduction Delayed ejaculation is a small but important subsection of ejaculatory dysfunction, with prevalence estimated at 1–4%. It is most commonly defined by DSM‐IV‐TR criteria, as "a persistent delay in, or absence of, orgasm in a male following a normal sexual excitement phase during sexual activity that the clinician, taking into account the person's age, judges to be adequate in focus, intensity, and duration." The pathophysiology of delayed ejaculation is related to disruptions in ejaculatory apparatus, nervous transmission, hormonal or neurochemical ejaculatory control, or psychosocial factors. Aim To update the clinician on the evaluation and treatment of delayed ejaculation. Methods The keywords "delayed ejaculation" and "retarded ejaculation" were utilized to search Pubmed for relevant publications. Main Outcome Measures 319 results were generated from the search, and those publications judged relevant to the pathophysiology, epidemiology, evaluation, and treatment of delayed ejaculation were included in the review. Result 110 articles were ultimately selected for inclusion in this review. Conclusion The evaluation of this condition requires a focused history and physical, which includes a detailed sexual history, examination of the genitalia, and inquiry into the status of the partner. Laboratory tests are aimed at the detection of abnormalities in the blood count, glucose level, hormone levels, or kidney function. If a correctable etiology is discovered, treatment is directed towards the reversal of this condition. In some cases, the delayed ejaculation may be a lifelong problem. Also, in some cases the etiology of the delayed ejaculation may be irreversible, such as in the case of age‐related sensation loss or diabetes‐related neuropathy. In these instances treatment may require a combination of behavioral modification, sexual therapy, or perhaps pharmaceutical drugs. Participation of the partner in therapy may sometimes be necessary. Future investigations will continue to elucidate the complex biological and psychosocial factors which contribute to delayed ejaculation, leading to more effective treatments. Shin DH and Spitz A. The evaluation and treatment of delayed ejaculation. Sex Med Rev 2014;2:121–133.